(untitled) (Proceedings of Southern Federal University. Philology, 2021)
Proverbs and sayings are an ancient genre of folk art. They originated in a distant time, and have their roots deep into the centuries. Many of them appeared even when there was no written language. Proverbs and sayings characterize not only folk wisdom, but also determine the ethnic identity and national-cultural features of a particular people. Their edifying message is relevant in modern society, and the brevity and simplicity of rhyme allows people of different ethnic groups to spread on aphoristic sayings from generation to generation. The analyzed paremias containing the concept of “home” differ in thematic diversity and reflect the ethnic culture of the Kumyk people: their traditional values, worldview, religious and other foundations. The home for the native speaker of the national language consciousness is a part of the unchanging environment of a person, the sphere of his existence, as well as a source of practical use. The house is a symbol of constancy, reliability and a sense of security, belonging to the family, the genus. The system of moral and ethical values, which consists in proverbs and sayings, is the result of centuries of experience, which was formed by the people. In the modern world, when traditional values can be distorted, the study of such aphoristic genres as proverbs and sayings, in the aspect of reflecting moral, ethical and moral values in them, contributes to popular education, familiarity with certain customs that should not be dissolved in time. Key words: Kumyk paremia, Kumyk oral folk art, lexeme “house”, ethnoculture, moral values, expressiveness, imagery. DOI 10.18522/1995-0640-2021-3-10-21